Molecular Engineering Design for High-Performance Aqueous Zinc-Organic Battery - Sun, Tianjiang; Zhang, Weijia; Nian, Qingshun; Tao, Zhanliang (Nano-Micro Letters, 2023)
Novel small sulfur heterocyclic quinones (6a,16a-dihydrobenzo[b]naphtho[2′,3′:5,6][1,4]dithiino[2,3-i]thianthrene-5,7,9,14,16,18-hexaone (4S6Q) and benzo[b]naphtho[2′,3′:5,6][1,4]dithiino[2,3-i]thianthrene-5,9,14,18-tetraone (4S4Q)) are developed by molecule structural design method and as cathode for aqueous zinc-organic batteries. The conjugated thioether (–S–) bonds as connected units not only improve the conductivity of compounds but also inhibit their dissolution by both extended π-conjugated plane and constructed flexible molecular skeleton. Hence, the Zn//4S6Q and Zn//4S4Q batteries exhibit satisfactory electrochemical performance based on 3.5 mol L−1 (M) Zn(ClO4)2 electrolyte. For instance, the Zn//4S6Q battery obtains 240 and 208.6 mAh g−1 of discharge capacity at 150 mA g−1 and 30 A g−1, respectively. The excellent rate capability is ascribed to the fast reaction kinetics. This system displays a superlong life of 20,000 cycles with no capacity fading at 3 A g−1. Additionally, the H+-storage mechanism of the 4S6Q compound is demonstrated by ex situ analyses and density functional theory calculations. Impressively, the battery can normally work at − 60 °C benefiting from the anti-freezing electrolyte and maintain a high discharge capacity of 201.7 mAh g−1, which is 86.2% of discharge capacity at 25 °C. The cutting-edge electrochemical performances of these novel compounds make them alternative electrode materials for Zn-organic batteries. Highlights: 1 The conjugated thioether (–S–) bonds as connected units not only improve the conductivity of compounds but also inhibit their dissolution by both extended π-conjugated plane and constructed flexible molecular skeleton. 2 The Zn//4S6Q battery based on 3.5 M Zn(ClO4)2 electrolyte shows excellent rate capacity (208.6 mAh g−1 at 30 A g−1), superlong cycling life (> 20,000 cycles with no capacity fading), and impressive low-temperature performance (201.7 mAh g−1 at − 60 °C). 3 The H+-storage mechanism of 4S6Q compound is demonstrated by comprehensive characterizations.